BIONOMICS AND ABUNDANCE OF ANOPHELES MOSQUITOES IN BIHSUD DISTRICT, NANGARHAR AFGHANISTAN - Ziarat Gul Mansoor, Allah Nazar Atif,Muhammad Nasir Hamdard ,Ajmal Rasooly,Sifatullah ShakireSulaiman Haqyar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A scientific Survey for the collection of Anopheles Mosquitoes at district Bihsud was carried out from August 2017 to July 2018. This survey includes the sampling of adult mesquites, and identified a total of 6 species in three targeted villages i.e. Malik Bella, Belandghar and Daman. Adult mosquitoes were collected pyrethrum spray methods from Man- Biting rooms. Anopheles Mosquitoes collection comprised by the species were A. hyrcanus (15.67%) as the most abundant mosquito species followed by A. pulcherimus (15.28%), A. fluviatilis (14.80%), A. stephensi (14.68%), A. superpictus (14.63%,),A. culicifacies (13.53%), and A. subpictus (11.38%), of the total collection. During the study most of the species built up their population. The highest density was observed during the month of October 2017. During winter months the population density fined very low. A total of 3294 Anopheles species were collected at village Daman. A hyrcanus was (511, 15.51%) found to be the most abundant species then other species of Anopheles genus. While A. culicifacies was (429, 13.02%) comparatively least abundant species. A total of 3388 Anopheles species were collected in a survey at village Malik Bella. A.hyrcanus was (549, 16, 20%) found to be the most abundant species while A. subpictus was (390, 11.91) observed to be in a comparatively low abundance. A total of 3493 individuals belonging to various Anopheles species were collected in a survey at village Belandghar. A. fluviatilis was (530, 11.30%) found to be the most abundant species while A. subpictus was (402, 15.17%) the least abundant species.